Comparison of Granular Bone Grafts and Transverse Process Bone Grafts for Single-Segmental Thoracic Tuberculosis: A Retrospective Single-Center Comparative Study - Du, Xing; Ou, Yunsheng; Zhu, Yong; Luo, Wei; Jiang, Guanyin; Jiang, Dianming (Frontiers in Surgery, 2021)
Background: To compare the clinical efficacy of granular bone grafts and transverse process bone grafts for single-segmental thoracic tuberculosis (TB). Methods: The clinical records of 52 patients who were diagnosed with single-segmental thoracic TB and treated by one stage posterior debridement, bone graft fusion, and internal fixation in our department from 2015 to 2018 were retrospectively analyzed. Among them, 25 cases were in the granular bone graft group and 27 cases in the transverse processes bone graft group. Outcomes including the visual analog scale (VAS), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), neurological function, operative time, operative blood loss, hospital stay, Cobb angle, bone graft fusion time, and postoperative complications were all recorded and analyzed. Results: There were no significant differences in operative time, operative blood loss, and hospital stay between the two groups (P > 0.05). With an average follow-up of 18–33 months, all patients in the two groups showed significant improvement in VAS score, ESR, CRP, and neurological function compared with preoperative measurements (P < 0.05), however, no significant differences were found for the last follow-up (P > 0.05). The two groups showed similar Cobb angle correction (P > 0.05), but the granular bone graft group had a larger Cobb angle loss than the transverse processes bone graft group (P < 0.05). The bone graft fusion time of the granular bone graft group was shorter than that of the transverse processes bone graft group (P < 0.05). No significant difference was found in the postoperative complications rate between the two groups (P > 0.05). Conclusion: Granular bone grafts and transverse process bone grafts may achieve comparable clinical efficacy for single-segmental thoracic TB, but the former method had a shorter bone fusion time.